The driving forces behind the prices of major cryptocurrencies: Evidence from the past five years - Medina Ayta Mohammed; Carmen De Pablos Heredero; José Luis Montes Botella (Intangible Capital)
Purpose: The primary objective of this study is to uncover the complex relationship between cryptocurrency prices and significant global events that transpired within the past five years. These events encompass a wide spectrum, including political and global health crises, the public disclosure of multinational enterprises' investments in cryptocurrencies, and the influence of macroeconomic indicators. Beyond the exclusive focus on Bitcoin, this study adopts a more comprehensive approach encompassing various cryptocurrencies.